Предмет:
МатематикаАвтор:
smokeyg4nnОтвет:
Пошаговое объяснение:
вот
Автор:
tatianaholtОтвет: y(-3)=-20 - yнаим.
Пошаговое объяснение:
y=3x²+18x+7 [-5;-1]
y'=6x+18=6*(x+3)=0
6*(x+3)=0 |÷6
x+3=0
x=-3 ∈[-5;-3] ⇒
y(-5)=3*(-5)²+18*(-5)+7=3*25-90+7=75-83=-8.
y(-3)=3*(-3)²+18*(-3)+7=3*9-54+7=27-47=-20=yнаим.
y(-1)=3*(-1)²+18*(-1)+7=3*1-18+7=3-11=-8.
Автор:
clementineДобавить свой ответ
Предмет:
ИнформатикаАвтор:
nylahbenderОтветов:
Смотреть
Предмет:
Английский языкАвтор:
ozzieОтветов:
Смотреть
Предмет:
МатематикаАвтор:
jaggerandersenОтветов:
Смотреть